PENGARUH KEPEMIMPINAN, KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN SIKKA - Amir Djonu (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The purpose of this study was to test the effect of leadership on performance of employees Ravenue Financial Management and Regional Assests Official in Sikka, communication on performance of employess Ravenue Financial Management and Regional Assets Official in Sikka, work motivation on performance of employess Revenue Financial Management and Regional Assets in Sikka, leadership, communication, and motivation work together/ simultaneously on performance of employees Revenue Financial Management and Regional Asset Official in Sikka. The population in this study were all employees at the Ravenue of Financial Management and Regional Assets Official in Sikka which totaling 110 and 86 people of that number research sample used proportionate random sampling method with error level of 5%. The researcher used Multiple Linear Regression Analysis, t Test, F Test and Analysis of Coefficient of Determination. The analysis was found that: The effect of leadership was positive and significant on performance of employee Ravenue Financial Management and Regional Asset Official in Sikka, the effect of communication was positive and non significant on performance of employee Ravenue Financial Management and Regional Asset Official in Sikka,the effect of work motivation was positive   and non significant on performance of employee Ravenue Financial Management and Regional Asset Official in Sikka, leadership, communication, and motivation work together / simultaneous was positive and significant on performance of employee Ravenue Financial Management and Regional Asset Official in Sikka. It was recommended that the leadership of these three variables can manage the employees to work based on the duties and each functions in order to achieve organizational goals.